Explaining the outcomes of the 'Clean India' campaign: institutional behaviour and sanitation transformation in India. Issue 5 (30th September 2019) - Curtis, Val
Abstract : Introduction: Many less developed countries are struggling to provide universal access to safe sanitation, but in the past 5 years India has almost reached its target of eliminating open defaecation. Objective: To understand how the Indian government effected this sanitation transformation. Methods: The study employed interviews with 17 actors in the government's 'Clean India' programme across the national capital and four states, which were analysed using a theory of change grounded in Behaviour Centred Design. Results: The Swachh Bharat Mission (Gramin) claims to have improved the coverage of toilets in rural India from 39% to over 95% of households between 2014 and mid-2019. From interviews with relevant actors we constructed a theory of change for the programme, in which high-level political support and disruptive leadership changed environments in districts, which led to psychological changes in district officials. This, in turn, led to changed behaviour for sanitation programming. The prime minister set an ambitious goal of eliminating open defaecation by the 150th birthday of Mahatma Gandhi (October 2019). This galvanised government bureaucracy, while early success in 100 flagship districts reduced the scepticism of government employees, a cadre of 500 young professionals placed in districts imparted new ideas and energy, social and mass media were used to inform and motivate the public, and new norms of ethical behaviour were demonstrated by leaders. As a result, district officials became emotionally involved in the programme and felt pride at their achievement in ridding villages of open defaecation. Conclusions: Though many challenges remain, governments seeking to achieve the sustainable development goal of universal access to safe sanitation can emulate the success of India's Swachh Bharat Mission .